Reliability considerations in restructured power systems with wind generation - Mehrtash, Amir. (2013)
Addition of intermittent renewable resources and power system restructuring will have significant impact on system operation. Techniques for system planning and operation should therefore incorporate these changes appropriately. This research focuses on developing new models and techniques for reliability considerations to be used in power system planning and operation in this new environment. This research first reviews the work done in the modeling of intermittent renewable energy sources. As wind is the most common and cost-effective renewable energy resource in power systems, the studies focus on wind energy and assessment of its intermittent behavior, with the thinking that subsequently the results can be extended to other intermittent renewable energy resources. Power system restructuring and deregulation have emerged to maximize consumer choice, promote competition, and improve the quality of services and the efficiency of the electric enterprises. In this new environment, a generation system is segregated into different companies and the major concern of customers is their individual load point reliability rather than the total system reliability. Due to these new issues created by power system restructuring, the conventional techniques cannot be directly used for load point reliability evaluation. Reliability Network Equivalent Techniques (RNET) have been introduced to incorporate the changes caused by restructuring in power system planning. The unreliability contributions from Equivalent Multistate Generation Provider (EMGP) and Equivalent Multistate Transmission Provider (EMTP) to each load point can be obtained using these techniques. In this thesis, the RNET are improved to include the effect of wind speed in generation systems. These equivalent models are developed further and extended in this research to lead to more precise and applicable results.